Video Games and Learning About Climate Change - Garrett W. Richards; Michael Long (The University of Alabama, 2021)
It is critical to pursue climate change education through a variety of methods, with a variety of audiences, and in a variety of contexts. This short perspectives article describes our experiences as an early-career climate change researcher and an independent game designer in responding to a community challenge posed by a nonprofit organization focused on the potential positive social impact of video games. This was an excellent opportunity to do some strategic thinking around climate change education (e.g., conceptualizing "butterfly effects"). However, we ultimately observed shortcomings in the supports available from educational and funding organizations for climate change knowledge translation using this cutting-edge medium, despite the urgency of climate change. This article follows a dialogic style, alternating between the two authors in order to provide an authentic account of our individual and collective experiences.